Umbilical Cord Blood Lead Levels and Neonatal Behaviour - M. L. de Cáceres; F. Botet; C. Costas; S. Rosales (Behavioural Neurology)
Negative correlations have been found between cord blood lead levels and scores on the Brazelton Neonatal Behaviour Assessment in 30 otherwise healthy newborns. Items in the Habituation, Orientation and Regulation of state clusters, particularly those items related to self-regulatory, self-quieting and auditory habituation, showed lower scores (worse performance) in those newborns with higher cord blood lead levels. These disturbances are potentially important since this type of behavior may interfere with the normal process of adaptation to their environment, leading to a less than optimal bonding between newborns and their carers.